Creative destruction: Screen production research, theory and affect. (1st March 2016) - Berkeley, Leo; Wood, Martin; Glisovic, Smiljana
The documentary film 600 Mills was explicitly funded and produced as an academic research project, designed to investigate, through cinematic means, the decline of the textile industry in the Melbourne suburb of Brunswick. Drawing on the work of Thrift, Deleuze and Guattari, Massumi and others, it is argued that the film production process uses 'affect' as a form of sensory knowing that can engage with relevant theory and be used to conceive of film-making as a valid form of academic research. This article discusses the approach taken by three film-maker researchers in making a film that, instead of using the medium to convey information or communicate research findings gathered through other means, seeks to use the creative possibilities of film production to convey knowledge about a complex human, social and historical process.